On the possibilities of using some modern three-dimensional modeling means in forensic examination - Dmitry S Afonin; Iryna V Hora; Valerii A Kolesnyk; Inna I Popovych; Iryna V Kuchynska (Wolters Kluwer Medknow Publications, 2022)
Background: The paper examines the state and prospects of using 3D modeling in solving identification, classification, diagnostic and situational tasks of forensic examination. Aims and Objectives: The aim of this study is to analyze the world expert practice of using scientific and technical means of three-dimensional modeling in solving problems of forensic examination, using the example of our country, the leading countries of Europe, as well as the United States. Materials and Methods: The empirical basis of the study is the results of the systematization of scientific and technical means for 3D modeling in solving identification, classification, diagnostic and situational problems of forensic examinations used in the expert practice of Ukraine, the United Kingdom, France, Germany, and the USA. Results: The systematization of modern scientific and technical means for 3D modeling, used in solving identification, classification, diagnostic and situational tasks of forensic examination, has been carried out. We analyzed and identified 3D modeling software that most fully meets the requirements of effective forensic expert activities. The features of the use of effective 3D modeling mean for solving identification, classification, diagnostic and situational tasks of forensic examination, namely the software systems "ToolScan" and "TrasoScan", and the SketchUp program have been disclosed. Conclusion: The introduction of the SketchUp 8 software into forensic expert activities will increase the effectiveness of the modeling method in forensic examinations, which, in turn, will have an impact on the effectiveness of expert conclusions, increase their evidentiary value and, as a result, contribute to the entire process of a criminal investigation.